Interleukin 31 is involved in intrahepatic cholestasis of pregnancy. (3rd May 2017) - Basile, F.; Santamaria, A.; Mannucci, C.; Rizzo, L.; Gangemi, S.; D'anna, R.; Arcoraci, V.
Abstract: Intrahepatic cholestasis of pregnancy (ICP) is a liver disorder characterized by maternal itching and altered liver function. Interleukin (IL)-31 is known to be involved in the pathogenesis of pruritic inflammatory skin diseases. In a three-year period, 13 women with a singleton pregnancy and a diagnosis of intrahepatic cholestasis (ICP) were enrolled together with 26 healthy single pregnant women who concluded an uncomplicated pregnancy. The inclusion criteria were itching and elevated levels of liver transaminases. Median serum levels of IL-31 were significantly higher in ICP patients than in the control group ( p  = 0.004). Furthermore, IL-31 values were directly dependent on liver transaminase levels.